Desain lapisan Perkerasan Jalan Pada Ruas Jalan Desa Mbangga – Woloboa Kecamatan Wolowaru Kabupaten Ende - Radja, Veronika Miana; sydin, Thomas Aquino A.; Gado, Alfridus (TEKNOSIAR, 2023)
The Mbangga-Woloboa road section, Rindiwawo Village, Wolowaru District is included in the local road type with rigid pavement and a road width of 3 meters. Every year the condition of the Mbangga-Woloboa road section experiences damage, where several parts of the road have many holes and when it rains there are lots of puddles of water, which is very disturbing for road users. Even though the Ministry of Public Works, with the available funds, has repaired the existing damage by overlaying it repeatedly, it has not been able to solve the existing problem completely because the road condition has deteriorated again before it reaches its design life. Therefore, it needs to be redesigned by repairing the subgrade layer and replacing the road surface layer with new rigid pavement according to the load of vehicles passing through the road. So by using the AASHTO method, the traffic growth rate (i) of the planned road is 5.23% per year with collector road class. The effective Resilient Modulus (MR) value on the road section is 2770 psi with a CBR value of 1.87%, and DDT 2.70 kg/cm2. The thickness of the pavement layer is found to be D1 = 13 cm, D2 = 20 cm, and D3 = 41 cm.